2020
DOI: 10.1002/bit.27575
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Pichia pastoris for malic acid production from methanol

Abstract: The application of rational design in reallocating metabolic flux to accumulate desired chemicals is always restricted by the native regulatory network. In this study, recombinant Pichia pastoris was constructed for malic acid production from sole methanol through rational redistribution of metabolic flux. Different malic acid accumulation modules were systematically evaluated and optimized in P. pastoris. The recombinant PP-CM301 could produce 8.55 g/L malic acid from glucose, which showed a 3.45-fold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 67 publications
1
65
0
Order By: Relevance
“…The coding sequences were individually placed under the control of the strong AOX1 promoters and integrated into the genome of P. pastoris. In order to increase the e ciency of homologous recombination (HR), the KU70 mutant strain (Δku70) which has impaired nonhomologous end joining (NHEJ) was used as a parent strain (Guo et al 2021;Weninger et al 2018). The individual overexpression of ADCs from B. paralicheniformis, B. subtilis and C. glutamicum enabled the accumulation of β-alanine after 6 d of fermentation when feeding the strains with methanol (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coding sequences were individually placed under the control of the strong AOX1 promoters and integrated into the genome of P. pastoris. In order to increase the e ciency of homologous recombination (HR), the KU70 mutant strain (Δku70) which has impaired nonhomologous end joining (NHEJ) was used as a parent strain (Guo et al 2021;Weninger et al 2018). The individual overexpression of ADCs from B. paralicheniformis, B. subtilis and C. glutamicum enabled the accumulation of β-alanine after 6 d of fermentation when feeding the strains with methanol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on metabolite production in fermentations of engineered P. pastoris mainly remain at the proof-of-concept stage, with titers usually lower than 1 g/L, especially when methanol is used as substrate (Gao et al 2021). Several recent studies reported gram per liter metabolites production in shake asks, with examples including isobutanol (Siripong et al 2020;Siripong et al 2018), malic acid (Guo et al 2021), and D-lactic acid (Yamada et al 2019). Unfortunately, the chemicals production potential of these recombinant P. pastoris strains was not fully evaluated by cultivation on the fermenter scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, DAS is not exploited as a biocatalyst. However, Pichia pastoris , a kind of methylotrophic yeast, have been engineered to produce chemicals from methanol using XuMP [ 81 ]. Similar to DAS, transketolase (TK, EC 2.2.1.1) can catalyze the reaction of D-fructose-6-phosphate or L-sorbose with formaldehyde to generate dihydroxyacetone [ 82 ].…”
Section: C-c Ligases For Formaldehyde Biotransformationmentioning
confidence: 99%